The effect of local anesthetic solution volume applied in retrobulbar block in cataract surgery on the duration of anesthesia and patient comfort - Kayaalti,Selda (2020)
Abstract Objective: To compare the use of 2 different local anesthetic solution (LAS) volumes of 1.5 mL and 3 mL in retrobulbar block in patients undergoing cataract surgery in terms of anesthesia, akinesia, and pain levels. Methods: 80 patients between 18-90 years old, ASA I-II-III, were included in the study. For retrobulbar anesthesia, 1.5 mL LAS was applied to one group (Group LV), and 3 mL LAS to the other group (Group HV). The patients' ocular and eyelid motion scores were evaluated and recorded in the first, third, fifth, and tenth minutes after the block, and at 30-minute intervals for 4 hours post-operatively. One day later, the first hour of analgesic need and the number of times they took analgesic agents were asked and recorded. In addition, side effects were questioned and recorded. Results: The 39 (48.75%) patients were male and 41 (51.25%) patients were female. The criteria determined in terms of ocular motor score after the retrobulbar block (ocular motor score≤4) were met in 92.5% of patients in Group LV in all patients in Group HV, and the time to fulfill the determined criteria in Group HV was found to be significantly lower compared to Group LV (p=0.004). The movements of the eye in all direction except the inward movement recovered in Group LV in a significantly shorter time than Group HV (p=0.004). There was no significant difference in pain levels and side effects between the groups (p=0.34). Conclusions: After 1.5 mL LAS administration in retrobulbar block, adequate akinesia was not achieved in about one tenth of patients, but no significant difference was found between 1.5 mL and 3 mL LAS volumes in analgesic efficacy and side effects.